Internet Video Pre-Movie Advertising Service Strategy - Quan Miao; Shuo Wang (Dianxin kexue)
Internet video has presented a huge development potential,which makes advertising the main way of profit.As no related laws and regulations exist in our country,the pre-movie advertisement affects user experience seriously,resulting in prominent disputes and contradictions.Therefore,internet video pre-movie advertising service strategy was developed.The business model for video site and its impact on advertising service,the advertising style,timing and relevance to program were analyzed,under the overall environment of internet development.Finally,executable solution was proposed.